Floristic composition & tree biomass in relations to the physico-chemical properties of soil in Taman Negara Pahang, Malaysia / Nor Farika Zani - Zani, Nor Farika (2015)
Taman Negara Pahang is the Malaysian tropical rainforests that are remarkably known for its complex and diverse ecosystem. However, research on species composition and biomass in different forest types in Taman Negara Pahang is still lacking. Furthermore, research on soil physico-chemical properties and the relation with the species composition in Taman Negara Pahang have not been extensively documented. Therefore, this study was conducted to determine the level of tree species composition and diversity, tree biomass and the relation between the floristic compositions with the physicochemical properties of soil in Taman Negara Pahang. Field data were collected from a twenty 0.04-ha permanent plots (20 m x 20 m) that were established in three forest types; lowland dipterocarp, riparian and hill dipterocarp forests. All trees with a diameter at breast height (DBH) greater than 10 cm in the sampled plots were measured. Soil samples (0-15 cm) were collected for each study site. A total of 1283 individuals belong to 54 families, 146 genera and 314 species were enumerated. Based on the important value index (IVI) values, the most dominant species in lowland dipterocarp forest was Elateriospermumtapos (Euphorbiaceae) (4.44%) whereas for riparian and hill dipterocarp forests were Dysoxylum arborescens (Meliaceae) (23.05%) and Shorea curtisii (Dipterocarpaceae) (7.65%), respectively. The Shannon diversity index (H’) values for lowland dipterocarp forest (4.84) was higher than riparian (3.38) and hill dipterocarp forests (4.48). In the case of forest biomass, hill dipterocarp forest attained the highest mean of above ground (AGB), below ground (BGB) and total tree biomass (TTB) with value of 400.97 t/ha, 85.27 t/ha and 585.25 t/ha, respectively. Biomass in these three forest types are significantly affected by species (p< 0.05), however not significantly affected by family (p>0.05). There is no significant interaction between forest type and family but significant different was detected between forest type and species (p< 0.05). In addition, this study demonstrated variations in the soil properties values within study areas. With respect to eigenvalues of Canonical correspondence analysis (CCA), the relationship between tree community and soil properties in the three study areas were considered as high. However, based on the cumulative percentage variance of species and tree community which is 54.9% indicate that there might be other factors that influence the pattern of species distribution in Taman Negara Pahang.